Ga‐68‐PSMA PET/CT in treatment‐naïve patients with prostate cancer: Which clinical parameters and risk stratification systems best predict PSMA‐positive metastases?. Issue 14 (5th July 2018) - Rogasch, Julian M.; Cash, Hannes; Zschaeck, Sebastian; Elezkurtaj, Sefer; Brenner, Winfried; Hamm, Bernd; Makowski, Marcus; Amthauer, Holger; Furth, Christian; Baur, Alexander D. J.
Abstract : Purpose: To evaluate the accuracy of clinical parameters and established pre‐treatment risk stratification systems for prostate cancer (PCa) in predicting PSMA‐positive metastases in men undergoing Ga‐68‐PSMA PET/CT as initial staging examination. Materials and Methods: A retrospective analysis in 108 consecutive treatment‐naïve patients with biopsy‐proven PCa undergoing Ga‐68‐PSMA PET/CT (median age, 72 years [range, 49‐82 years]) was performed. Prediction of PSMA‐positive metastases by serum PSA, clinical T stage (cT), ISUP group, percentage of positive biopsy cores, and derived risk scores (D'Amico risk classification system, Roach [RF], Yale formula [YF], and Briganti nomogram [BN]) was examined with ROC analysis. Results: Any PSMA‐positive metastases were found in 36 of 108 patients, including LN metastases in 28 patients, extrapelvic LN metastases in 15 patients, and organ metastases in 19 patients (bone, 19; lung, 1). AUCs for PSA, cT, ISUP, and percentage of positive biopsy cores regarding PSMA‐positive metastases did not differ significantly (range, 0.6‐0.8; each P > 0.05). D'Amico (AUC, 0.61‐0.64) was inferior to RF (0.76‐0.83), YF (0.81‐0.86), and BN (0.73 to 0.88; each P < 0.05). Among the 89 high‐risk patients (D'Amico), decision for or against PET imaging based on RF (cut‐off, >18.0), YF (>10.8), or BN (>8.0) would have prevented PSMA PET/CT in 4 (5%), 15 (17%), or 18 patients (20%), respectively, while preserving a sensitivity ≥95% for PSMA‐positive metastases. Conclusions: Clinical parameters and established risk stratification systems for PCa can predict Ga‐68‐PSMA PET‐positive metastases in treatment‐naïve patients. Especially YF and BN may improve identification of patients with the highest probability of metastatic disease detected by Ga‐68‐PSMA PET/CT.